Answer :



taking LCM



4x2 + 4ax + 2bx = - 2ab cross multiplying


4x2 + 4ax + 2bx + 2ab = 0


4x(x + a) + 2b(x + a) = 0 taking 4x common from first two terms and 2b from last two


(x + a) (4x + 2b) = 0


(x + a) = 0 or (4x + 2b) = 0



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses